Korean nursery rhymes : Wild geese, Land of goblins and other favorite songs and rhymes - Wright, Danielle; Acraman, Helen (Tokyo ; Rutland, Vermont : Tuttle Pub. ; North Clarendon, VT : Distributed by North American, Latin America & Europe, 2013)
An illustrated collection of fourteen nursery rhymes, plus notes on Korean culture and explanations of how the jump rope and hand clap games are played. Presented in Hanguel script, Romanized Korean, and English; accompanying CD contains recordings of all of the rhymes performed in Korean and English.
Butterfly -- Little one (traditional song) -- Our house (traditional song) -- Island baby / In-hyeon Han -- Here, there / Suk-kyeong Kim -- Land of goblins -- Monkey's bottom (traditional song) -- Cotton candy / Geun Jeong -- Wild Geese (traditional song) -- Spring in my hometown / by Weon-su Yi -- Twirling round (traditional song) -- Little fox (traditional song) -- Half moon / by Geuk-yeong Yun -- Land of white / by Seong-gyun Kim.
Keywords: Nursery rhymes, Korean; Children's poetry, Korean; Nursery rhymes; Korean language materials -- Bilingual; JUVENILE NONFICTION / Foreign Language Study / General; EDUCATION / Preschool & Kindergarten